Population genomic variation reveals roles of history, adaptation and ploidy in switchgrass - Grabowski, Paul P.; Morris, Geoffrey P.; Casler, Michael D.; Borevitz, Justin O. (My University, 2014)
Geographic patterns of genetic variation are shaped by multiple evolutionary processes, including genetic drift, migration and natural selection. Switchgrass (Panicum virgatum L.) has strong genetic and adaptive differentiation despite life history characteristics that promote high levels of gene flow and can homogenize intraspecific differences, such as wind-pollination and self-incompatibility. To better understand how historical and contemporary factors shape variation in switchgrass, we use genotyping-by-sequencing to characterize switchgrass from across its range at 98 042 SNPs. Population structuring reflects biogeographic and ploidy differences within and between switchgrass ecotypes and indicates that biogeographic history, ploidy incompatibilities and differential adaptation each have important roles in shaping ecotypic differentiation in switchgrass. At one extreme, we determine that two Panicum taxa are not separate species but are actually conspecific, ecologically divergent types of switchgrass adapted to the extreme conditions of coastal sand dune habitats. Conversely, we identify natural hybrids among lowland and upland ecotypes and visualize their genome-wide patterns of admixture. Furthermore, we determine that genetic differentiation between primarily tetraploid and octoploid lineages is not caused solely by ploidy differences. Rather, genetic diversity in primarily octoploid lineages is consistent with a history of admixture. This suggests that polyploidy in switchgrass is promoted by admixture of diverged lineages, which may be important for maintaining genetic differentiation between switchgrass ecotypes where they are sympatric. These results provide new insights into the mechanisms shaping variation in widespread species and provide a foundation for dissecting the genetic basis of adaptation in switchgrass.
Citation: Grabowski, Paul P., Geoffrey P. Morris, Michael D. Casler, and Justin O. Borevitz. “Population Genomic Variation Reveals Roles of History, Adaptation and Ploidy in Switchgrass.” Molecular Ecology 23, no. 16 (2014): 4059–73. https://doi.org/10.1111/mec.12845.
Keywords: Ecotypes; Genotyping-by-sequencing; Perennial grass; Polyploidy